Hacking a terror network the silent threat of covert channels - Rogers, Russ (Syngress Pub., 2005)
Annotation Written by a certified Arabic linguist from the Defense Language Institute with extensive background in decoding encrypted communications, this cyber-thriller uses a fictional narrative to provide a fascinating and realistic "insider's look" into technically sophisticated covert terrorist communications over the Internet. The accompanying CD-ROM allows readers to "hack along" with the story line, by viewing the same Web sites described in the book containing encrypted, covert communications. Hacking a Terror NETWORK addresses the technical possibilities of Covert Channels in combination with a very real concern: Terrorism. The fictional story follows the planning of a terrorist plot against the United States where the terrorists use various means of Covert Channels to communicate and hide their trail. Loyal US agents must locate and decode these terrorist plots before innocent American citizens are harmed. The technology covered in the book is both real and thought provoking. Readers can realize the threat posed by these technologies by using the information included in the CD-ROM. The fictional websites, transfer logs, and other technical information are given exactly as they would be found in the real world, leaving the reader to test their own ability to decode the terrorist plot. Cyber-Thriller focusing on increasing threat of terrorism throughout the world. Provides a fascinating look at covert forms of communications used by terrorists over the Internet. Accompanying CD-ROM allows users to "hack along" with the fictional narrative within the book to decrypyt
Includes link to CD content. - Title from title screen. - Title from book cover on Web Page (viewed Aug. 23, 2005)
Keywords: Computer networks / Security measures; Computer security; Cyberterrorism; Internet / Security measures; Electronic books; Computer networks -- Security measures; Internet -- Security measures